The Influence Of Campus Wifi Facilities On Students Learning Motivation In State University Surabaya - Zunia Faradinna Ikrima; Derra Febrilia Dwi Rahma Sokhib; Diva Meylia Putri Indraswari; Triesninda Pahlevi; Farij Ibadil Maula (CV. Rayyan Dwi Bharata, 2024)
This study aims to determine the effect of WiFi facilities in schools on student motivation to complete the Office Administration Education study program as well as factors that moderate or mediate the influence of the program. The analysis method used is a quantitative approach using purposive sampling to produce non-probabilistic sample data. The sample of this study consisted of 188 master students from the Department of Educational Administration Class of 2022, and 65 people were selected as a representative sample from a total of ten different classes. Data were collected using a questionnaire selected based on relevant indicators. Using SPSS software, data analysis was conducted using classical assumptions such as heteroscedasticity, multicollinearity, and normality. Reliability and validity of the instrument were assessed using a feasibility trial assessment. A Likert scale was used to rank the statements in the instrument. The results show that there is a positive impact of WiFi services on students' learning motivation and tenacity level.